Human Oral Buccal Microbiomes Are Associated with Farmworker Status and Azinphos-Methyl Agricultural Pesticide Exposure - Stanaway, Ian B. (Appl Environ Microbiol, 2016)
In a longitudinal agricultural community cohort sampling of 65 adult farmworkers and 52 adult nonfarmworkers, we investigated agricultural pesticide exposure-associated changes in the oral buccal microbiota. We found a seasonally persistent association between the detected blood concentration of the insecticide azinphos-methyl and the taxonomic composition of the buccal swab oral microbiome. Blood and buccal samples were collected concurrently from individual subjects in two seasons, spring/summer 2005 and winter 2006. Mass spectrometry quantified blood concentrations of the organophosphate insecticide azinphos-methyl. Buccal oral microbiome samples were 16S rRNA gene DNA sequenced, assigned to the bacterial taxonomy, and analyzed after “centered-log-ratio” transformation to handle the compositional nature of the proportional abundances of bacteria per sample. Nonparametric analysis of the transformed microbiome data for individuals with and without azinphos-methyl blood detection showed significant perturbations in seven common bacterial taxa (>0.5% of sample mean read depth), including significant reductions in members of the common oral bacterial genus Streptococcus. Diversity in centered-log-ratio composition between individuals' microbiomes was also investigated using principal-component analysis (PCA) to reveal two primary PCA clusters of microbiome types. The spring/summer “exposed” microbiome cluster with significantly less bacterial diversity was enriched for farmworkers and contained 27 of the 30 individuals who also had azinphos-methyl agricultural pesticide exposure detected in the blood. IMPORTANCE In this study, we show in human subjects that organophosphate pesticide exposure is associated with large-scale significant alterations of the oral buccal microbiota composition, with extinctions of whole taxa suggested in some individuals. The persistence of this association from the spring/summer to the winter also suggests that long-lasting effects on the commensal microbiota have occurred. The important health-related outcomes of these agricultural community individuals' pesticide-associated microbiome perturbations are not understood at this time. Future investigations should index medical and dental records for common and chronic diseases that may be interactively caused by this association between pesticide exposure and microbiome alteration.